ANALYSIS OF THE COST EFFECTIVENESS OF THERAPY IN HYPERTENSION AND TYPE 2 DIABETES MELLITUS PATIENTS IN OUTSTANDING INSTALLATION RSUD TOTO KABILA - Madania Madania; Asnia Bangol; Ana Diantika (Universitas Negeri Gorontalo, 2022)
Hypertension and diabetes mellitus are degenerative diseases where various therapies are certainly used so that the effectiveness of each drug and the costs incurred need to be considered. The more treatments used, the more costs will be incurred. Therefore, a pharmacoeconomic analysis needs to be carried out to assist decision making in performing therapy. This research was a non-experimental research with descriptive analysis design. Data collection was retrospective by tracing previous documents sourced from medical records of patients with hypertension and Type 2 Diabetes Mellitus (DM) at the Outpatient Installation of Toto Kabila Regional General Hospital for the period of October to December 2020. Samples were taken by purposive sampling technique and then the data obtained were analyzed by calculating the direct medical costs and drug effectiveness. Data analysis from this study used Cost Effectiveness Analysis (CEA) and was continued in the form of ratio, namely Average Cost Effectiveness Ratio (ACER) or Incremental Cost Effectiveness ratio (ICER). The results showed that in hypertension, drug therapy used were Amlodipine (47.8%) and Candesartan (52.2%), while in Type 2 DM therapy were the combination of Metformin and Glimepiride (68.9%) and the combination of Insulin-Aspart and Insulin Detemir (31.1%). The direct medical cost of hypertension therapy with Amlodipine was Rp. 184.921, and Candesartan was Rp. 158.159. As for the Type 2 DM therapy, the cost of Metformin-Glimepiride combination was Rp. 168.253,226 and the combination of Insulin-Aspart and Insulin-Detemir of Rp. 1.077.259. The results of the cost effectiveness calculation show that Candesartan is more cost-effective than Amlodipine, while the combination of Metformin-Glimepirid is more cost-effective than the combination of Insulin-Aspart and Insulin-Detemir.